The development of biologics to target SARS-CoV2: Treatment potential of antibodies in patient groups with poor immune response - William Migo; Marko Boskovic; Robert Likic (Elsevier, 2021)
Development of novel antibodies to combat the novel SARS-CoV-2 virus is ongoing. Importantly, particular subgroups are more prone to severe disease, namely patients with poor immune responses. This includes cancer patients with solid and haematological disease, solid organ transplant (SOT) patients and those with congenital or acquired immunodeficiency. Outcomes for patients with poor immune responses receiving antibody therapy for underlying disease and SARS-CoV-2 severe infection are undergoing investigation. The objective of this study was to perform a search on patients with poor immune responses with severe SARS-CoV-2 infection, to assess if antibody therapy is beneficial in such populations. We performed searches using PubMED and medrXiv up to May 2021 of patients with solid and hematologic malignancy, SOT patients and acquired or congenital immunodeficiency. The primary outcome was to assess if antibody therapy was included during SARS-CoV-2 infection and the clinical outcomes of such treatment in this population. Here we find that there is a repurposing of monoclonal antibodies to target cytokine release syndrome, along with the use of convalescent plasma (CP). Despite CP demonstrating promising results, we reiterate evidence that CP forces mutational escape and subsequent variant development. Repurposing of antibody therapies (such as Tocilizumab) proved effective, especially in SOT patients. This also potentially opens an avenue for the use of anti-SARS-CoV-2 spike protein neutralizing monoclonal antibodies; however, studies have yet to focus on patients with poor immune responses as a subpopulation.